Measured (and estimated) glomerular filtration rate: reference values in West Africa - Yayo, Eric; Ayé, Mireille; Yao, Carine; Gnionsahé, Appolinaire; Attoungbré, Marie-Laure; Cavalier, Etienne; Pottel, Hans; Monnet, Dagui; Delanaye, Pierre (Nephrology, dialysis, transplantation, 2018)
Establishment of normal reference values for glomerular filtration rate (GFR) is mandatory in nephrology. However, no data are available for measured GFR (mGFR) in Africa. GFR was measured in 237 healthy adult subjects (103 women and 134 men, mean age 34 ± 10 years) by iohexol plasma clearance. The mean mGFR was 103 ± 17 mL/min/1.73 m2 and the median value was 103 mL/min/1.73 m2 (2.5th and 97.5th percentiles are 76 and 137 mL/min/1.73 m2, respectively). No significant difference in mGFR results was observed in patients < 40 years of age, whereas a significant decline in mGFR was observed after 40 years of age. There was no significant difference between mGFR in men and women. Normal GFR values and descriptions of percentiles are now available for West Africa. As in Caucasians, no significant difference was observed between men and women. Moreover, the same age-associated decline in mGFR is also observed after 40 years of age, as in Caucasians.